2000
DOI: 10.1017/s0033291799002524
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life impairments associated with diagnostic criteria for traumatic grief

Abstract: The results suggest that a traumatic grief diagnosis is significantly associated with quality of life impairments. These findings provide evidence supporting the criterion validity of the proposed consensus criteria and the newly developed diagnostic interview for traumatic grief the Traumatic Grief Evaluation of Response to Loss (TRGR2L).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 20 publications
4
119
1
2
Order By: Relevance
“…As noted earlier, however, the concept of pathological grief is coming to be seen as a separate diagnostic entity that is deserving of dedicated study, 38 with TG specifically defined as a distinct cluster of symptoms-as a syndrome-that both predicts and includes future morbidity. [39][40][41][42][43][44][45][46][47] According to consensus criteria for the disorder, 45 which are summarized in the text box, TG is a stress response syndrome whose symptoms include (1) separation distress (for example, yearning, searching for the deceased, excessive loneliness resulting from the loss) and (2) traumatic distress (for example, feelings of numbness, disbelief about the loss, being stunned or dazed, having a fragmented sense of security and trust, having intrusive thoughts about the deceased).…”
Section: Pathological Grief In the General Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted earlier, however, the concept of pathological grief is coming to be seen as a separate diagnostic entity that is deserving of dedicated study, 38 with TG specifically defined as a distinct cluster of symptoms-as a syndrome-that both predicts and includes future morbidity. [39][40][41][42][43][44][45][46][47] According to consensus criteria for the disorder, 45 which are summarized in the text box, TG is a stress response syndrome whose symptoms include (1) separation distress (for example, yearning, searching for the deceased, excessive loneliness resulting from the loss) and (2) traumatic distress (for example, feelings of numbness, disbelief about the loss, being stunned or dazed, having a fragmented sense of security and trust, having intrusive thoughts about the deceased).…”
Section: Pathological Grief In the General Populationmentioning
confidence: 99%
“…38 In this context, bereavement experts studying grief in elderly adults have recently developed the concept of "traumatic grief" (TG), a pathological grief response that is distinct from depression or anxiety and that may be the operant risk factor for the negative health effects of bereavement. [39][40][41][42][43][44][45][46][47] These studies show a compelling relationship between symptoms of TG and morbidity in the bereaved, thereby suggesting that grief reactions deserve focused and qualitative study, especially in vulnerable populations.…”
mentioning
confidence: 99%
“…Primarily based on data from widows and widowers, both teams propose criteria for Complicated Grief Disorder, and both argue that the disorder is a separate clinical entity because it is clinically distinct from depression, anxiety, post-traumatic stress disorder, and "normal" grief. Essentially, they argue that, while grief itself does not predict negative physical and psychological outcomes such as serious illness, suicidal ideation, and impairments in quality of life, the presence of complicated grief symptoms does predict such outcomes Prigerson et al, 1997Prigerson et al, , 1999Silverman et al, 2000).…”
Section: Medicalization Of Griefmentioning
confidence: 99%
“…Nevertheless, in recent years, a number of studies have shown that PTSD and CG are distinct disorders (Momartin, Silove, Manicavasagar, & Steel, 2004;Silverman, Jacobs, Kasl, Shear, Maciejewski, Noaghiul et al, 2000). For example, Silverman and colleagues (2000) found in their study of bereaved spouses (N = 85) that 18% met the criteria of CG and 7% met the criteria of PTSD at 4 months after their loss.…”
Section: Trauma and Bereavementmentioning
confidence: 99%